RESEÑA de: Pérez Bowie, José Antonio y Pardo García, Pedro Javier (eds.). Transescrituras audiovisuales. Madrid: Sial Pigmalión, 2015 - Vázquez Couto, David (Signa: Revista de la Asociación Española de Semiótica, 2017)
-